A Sense-based Registration Process for TDMA in IEEE 802.11 Network - Rizal Fathoni Aji; Heru Suhartanto; Setiadi Yazid (Institute of Advanced Engineering and Science, 2018)
TDMA implementation offer better fairness and throughput in IEEE 802.11. To implement TDMA, new registration process is needed, because current registration mechanism can disrupt TDMA process. This paper proposes a sense-based TDMA registration process using service slot and random timer. Simulation result shows, by using our mechanism, we can reduce the number of unused timeslot, and for 10 new nodes, each node only need 7 ms to complete the registration process.